2020
DOI: 10.1371/journal.pone.0229777
|View full text |Cite
|
Sign up to set email alerts
|

Natural history matters: Plastics in estuarine fish and sediments at the mouth of an urban watershed

Abstract: The extent to which small plastics and potentially associated compounds are entering coastal food webs, especially in estuarine systems, is only beginning to be realized. This study examined an estuarine reach at the mouth of urbanized Chollas Creek in San Diego, California to determine: 1) the extent and magnitude of microplastics pollution in estuarine sediments and fish, 2) the extent and magnitude of SVOC contamination in estuarine fish, and 3) whether fish preferentially ingested certain types of micropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…Regarding the representativeness of MPs types, fragments were by far the most abundant one in the estuarine sediments (st1), in agreement with findings from other studies (Vianello et al, 2013;Talley et al, 2020;Haddout et al, 2021;Liong et al, 2021). Conversely, fibers were less abundant, but consistently spread throughout the six stations.…”
Section: Distribution Patterns According To Types and Sizes Of Mpssupporting
confidence: 90%
“…Regarding the representativeness of MPs types, fragments were by far the most abundant one in the estuarine sediments (st1), in agreement with findings from other studies (Vianello et al, 2013;Talley et al, 2020;Haddout et al, 2021;Liong et al, 2021). Conversely, fibers were less abundant, but consistently spread throughout the six stations.…”
Section: Distribution Patterns According To Types and Sizes Of Mpssupporting
confidence: 90%
“…It has frequently been suggested that fish living in freshwater environments near urbanized regions have a higher risk of microplastic ingestion, and a direct relationship with the level of urbanization has been observed ( Silva-Cavalcanti et al, 2017 ; Souza, Corrêa & Smith, 2020 ; Galafassi et al, 2021 ). However, several studies present evidence that higher environmental concentrations of microplastics do not necessarily translate into higher ingestion by aquatic biota ( McNeish et al, 2018 ; Talley, Venuti & Whelan, 2020 ; Sembiring et al, 2020 ). Such is the case for our results because the microplastic numbers in the water were higher than in the stomachs.…”
Section: Discussionmentioning
confidence: 99%
“…Such is the case for our results because the microplastic numbers in the water were higher than in the stomachs. Life history may thus have an even more significant influence on the level of microplastic ingestion ( Talley, Venuti & Whelan, 2020 ). It is important to highlight here that more research is needed to obtain further information on microplastic ingestion by fish in Lake Titicaca.…”
Section: Discussionmentioning
confidence: 99%
“…The important sources of plastic pollution are agricultural mulching [59], sewage sludge disposal [60], wastewater treatment plants [61], informal landfills [62], and biowaste compost [63]. MPs are found in a variety of terrestrial environments, including home and garden soils [64], flood plain soils [65], remote high mountain soils [66], and industrial soils [67], as well as surface and deep ocean waters [68], lakes [69,70], mangroves [71], shorelines [72], and estuaries [73][74][75]. The studies conducted to examine the distribution of different sizes, forms, and types of MPs in estuaries across the world are presented in Table 1.…”
Section: Microplastic Pollution In Estuariesmentioning
confidence: 99%